Pembuatan Lemari untuk Masjid Ar Rahman Cibolang - Dani Mardiyana; Mulyadi; Heppi Familiana; Dwi Mardika Lestari; M Arvin Syarifuddin; Odi Akhyarsi; Muchammad Yusup Mubarok (LPPM POLITEKNIK LP3I, 2024)
The Ar Rahman Mosque is a newly built mosque, so the facilities inside are still inadequate. One of the essential facilities that is urgently needed but not yet available is a cabinet for storing Qur'ans, Islamic books, prayer garments (mukena), and sarongs. The construction of this cabinet is very important and urgent because it not only serves as a storage space but also as an effort to enhance cleanliness, neatness, and comfort within the mosque. The construction process of the mosque cabinet includes designing, creating patterns on plywood, cutting plywood according to the patterns, assembly, and painting. The resulting cabinet measures 800 mm in length, 350 mm in width, and 1200 mm in height. The completed cabinet has successfully addressed the mosque's storage issues for Qur'ans, Islamic books, sarongs, and prayer garments, making the mosque space tidier and providing convenience and comfort for the congregation in utilizing it.